Assessing the importance of male and female part-time work for the gender earnings gap in Britain - Karen Mumford; Peter N. Smith (Institute for the Study of Labor (IZA), 2007)
This study examines the role of individual characteristics, occupation, industry, region, and workplace characteristics in accounting for differences in hourly earnings between men and women in full and part-time jobs in Britain. A four-way gender-working time split (male full-timers, male part-timers, female full-timers and female part-timers) is considered, and allowance is explicitly made for the possibility of both workplace and occupational segregation across each group. Individual and workplace characteristics are shown to explain much of the earnings gaps examined. Within gender groups, the striking difference between full and part-time employees is that full-timers work in higher paying occupations than do part-timers. Also, occupational segregation makes a significant contribution to the earnings gap between male and female part-time employees but not for full-time workers. A further new result is that female workplace segregation contributes significantly to the full/part time earnings gap of both males and females. Part-time employees work in more feminised workplaces and their earnings are lower. By contrast, occupational segregation has little impact on the full-time/part-time earnings gap of either males or females. There remains, moreover, a substantial residual gender effect between male and female employees.
Keywords: 330; Lohndifferenzierung; Zeitlohn; Geschlechterdiskriminierung; Frauenarbeitslohn; Arbeitszeit; Teilzeitarbeit; Großbritannien